Synthesis and Characterization of Poly(DL-Lactic Acid) Nanoparticles Loaded with the Antituberculosis Drug Isoniazid - Burkeev, M. Zh.; Tazhbaev, E. M.; Zhaparova, L. Zh.; Zhappar, N. K.; Zhumagalieva, T. S. (Springer US, 2016)
The possibility of creating a new dosage form of the antituberculosis drug isoniazid using nanoparticles of the polymer poly(DL-lactic acid) was studied. It was shown that nanoprecipitation was promising for preparing nanoparticles and loading them with drugs.
Keywords: poly(DL-lactic acid); drug delivery; isoniazid; nanoparticles